In vitro somatic embryogenesis of common cabbage - Donato, Virginia Maria Tenório Sabino; Andrade, Arnóbio Gonçalves de; Cabral, José Barbosa; Alves, Gilberto Dias (Pesquisa Agropecuaria Brasileira, 2000)
The aim of this study was to obtain calluses and somatic embryos of common cabbage (Brassica oleracea L., var. leucocephala) and to characterize them by means of histological observations in vitro; foliar explants were cultivated under asseptic conditions in a nutritive MS medium supplemented with various combinations of 2,4-D/BAP and 2,4-D/KIN. During the induction phase of calluses (phase I), there was a development of calluses with embryogenic characteristics derived from the media (5.0 mg/L of 2,4-D), (1.0 mg/L of 2,4-D plus 0.1 mg/L of BAP), (1.0 mg/L of 2,4-D plus 1.0 mg/L of BAP) and (2.0 mg/L of 2,4-D plus 0.05 mg/L of BAP), that were chosen for subcultivation in regeneration media (phase II). In this phase, culture media were supplemented with reduced concentrations of 2,4-D, BAP and GA3, or they were totally deprived of these supplements. In this case, the calluses remained in cultivation for other 30 days. The calluses that were subcultivated in the regeneration media R3 (0.1 mg/L of BAP) and R8 (0.001 mg/L of 2,4-D plus 0.01 mg/L of BAP), derived from the induction media M16 (5.0 mg/L of 2,4-D) and M30 (1.0 and 1.0 mg/L of 2,4-D and BAP), respectively, developed structures similar to embryos. However, this histological characterization revealed the superiority of the interaction between the M30 and R8 media for regeneration of the calluses and somatic embryos.